The big humanities digital humanities/digital laboratories - Lane, Richard J. 1966- (Routledge, Taylor & Francis Group, 2017)
"This book offers an accessible introduction to the digital humanities, one of the fastest growing areas of literary studies. Lane's unique approach focuses on the technologies and new environment in which the DH largely takes place: the digital laboratory. He provides a brief history of DH, explains the methodologies of past and current DH projects, and offers detailed case studies and bibliographies. The focus on the digital laboratory space reveals affiliations with the research that has traditionally taken place in the sciences, as well as convergences with other fast-growing research spaces like innovation labs, fabrication labs, maker spaces, digital media labs, and change labs"--Provided by publisher.